2011
DOI: 10.1186/gb-2011-12-8-r74
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase inhibitor treatment restores chromosome territory positions and active chromosome dynamics in Hutchinson-Gilford progeria syndrome cells

Abstract: BackgroundHutchinson-Gilford progeria syndrome (HGPS) is a premature ageing syndrome that affects children leading to premature death, usually from heart infarction or strokes, making this syndrome similar to normative ageing. HGPS is commonly caused by a mutation in the A-type lamin gene, LMNA (G608G). This leads to the expression of an aberrant truncated lamin A protein, progerin. Progerin cannot be processed as wild-type pre-lamin A and remains farnesylated, leading to its aberrant behavior during interphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 55 publications
3
83
2
Order By: Relevance
“…DamID has revealed altered genomic interactions for wild-type lamin A compared with those of progerin (49). Treatment with farnesyl transferase inhibitors prevents the accumulation of farnesylated progerin, producing a less toxic mutant lamin A protein, and this also seems to restore the normal radial nuclear positions of chromosomes in the treated fibroblasts (61).…”
Section: Radial Nuclear Organization the Nuclear Periphery And Humamentioning
confidence: 99%
“…DamID has revealed altered genomic interactions for wild-type lamin A compared with those of progerin (49). Treatment with farnesyl transferase inhibitors prevents the accumulation of farnesylated progerin, producing a less toxic mutant lamin A protein, and this also seems to restore the normal radial nuclear positions of chromosomes in the treated fibroblasts (61).…”
Section: Radial Nuclear Organization the Nuclear Periphery And Humamentioning
confidence: 99%
“…Chromosome territories can reorganize within the nuclear volume upon stimulation of normal dermal fibroblasts into quiescence and senescence. 30,31 This reorganization occurred rapidly, taking only minutes in quiescent stimulated cells, demonstrating the dynamic nature of genome organization and its responsiveness to stimuli. Given this rapid and dynamic response and the importance of TOR in regulating cellular function, significant changes in both genome function and organization could result from TOR repression.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] It has been reported that nuclear positions of genes, chromatin domains and even entire chromosome territories can change during development and cell differentiation. 8,[12][13][14] As an alternative to movements of entire chromosome territories, it was suggested that they may occupy the same nuclear place before and after activation of genes carried by them, whereas giant chromatin loops may form upon transcriptional activation and move such genes far away from their carrier chromosome territory into a nuclear environment favorable for their transcriptional activation and/or the maintenance of transcription. It was hypothesized that giant loops would even allow the formation of co-regulated, spatial clusters of genes located on different chromosome territories.…”
Section: Introductionmentioning
confidence: 99%